Regulatory reforms of European network industries and the courts - Günther Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2010)
Regulatory reforms in European network industries are strongly influenced by legal decisions. The cases considered in this paper not only initiated the liberali-zation process of the markets for network services but also provided an impor-tant signaling function for the remaining regulatory problems: localization of network-specific market power, abolishment of grandfathering rights, ex ante regulation of network-specific market power instead of negotiated unregulated network access, incentive regulation instead of cost-based regulation. The process towards sector-symmetric market power regulation based on economi-cally founded principles gains increasing relevance. Nevertheless, there are fur-ther reform potentials to be exhausted in the future.
Older version: http://hdl.handle.net/10419/43129
Keywords: 330